2012
DOI: 10.1007/s10067-012-1984-6
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and cochlear function of patients with ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is a chronic systemic inflammatory disorder that primarily affects the spine and sacroiliac joints. Recent studies described audiovestibular impairment in AS patients. The aim of this study was to evaluate the hearing and function of the cochlear system in patients with AS. Thirty-seven AS patients and 20 healthy controls were evaluated prospectively. Otorhinolaryngologic examinations were performed in all patients together with pure tone audiometry, speech discrimination test, tymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
1
9
1
Order By: Relevance
“…In our review, we found evidence of an increased prevalence of sensorineural hearing loss in patients with AS, but not specifically its relationship with sudden SNHL. 42 …”
Section: Discussionmentioning
confidence: 99%
“…In our review, we found evidence of an increased prevalence of sensorineural hearing loss in patients with AS, but not specifically its relationship with sudden SNHL. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Sensorineural hearing loss has been reported in a number of chronic systemic inflammatory disorders such as ankylosing spondylitis and rheumatoid arthritis, but exact cause of underlying pathology is still unknown [24, 25]. However, immunomediated vasculitis in the inner ear and ototoxic medication used for treatment was postulated as causative agents in some.…”
Section: Discussionmentioning
confidence: 99%
“…According to Daglı et al [7] , high frequencies are organized in the basal part of the cochlea; therefore, the damage is in the outer hairy cells of basal and intermediate parts of the cochlea in patients with AS. Nevertheless, Kahveci et al [9] did not find any cochlear dysfunction in patients with AS with regard to the audiological and DPOAE results. They explained this with the multifactority of SNHL in AS (age, drugs, duration of the disease, duration of medication, acoustic trauma, and previous middle and inner ear infections).…”
Section: Discussionmentioning
confidence: 90%
“…They explained this with the multifactority of SNHL in AS (age, drugs, duration of the disease, duration of medication, acoustic trauma, and previous middle and inner ear infections). They added that another possible reason for obtaining normal DPOAE results might be owing to SNHL because of hairy cell dysfunction in the inner ear and synaptic or retro cochlear pathology [9] . During the course of AS, immunologic vasculitis, autoantibodies against the inner ear, and ototoxic effects of drugs may cause SNHL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation